The Morphophonemics of Vowel Compensatory Lengthening in Ekegusii - Komenda, S; Maroko, Geoffrey Mokua; Ndung’u, R. W. (International Journal of Education and Research, 2013)
Literature shows that not much is known about the prosodic systems in Ekegusii, a Bantu language spoken by about 2.2 million people in south western Kenya.This paper presents an analysis of vowel compensatory lengthening in Ekegusii. Synchronic evidence for hiatus resolution strategies is provided in order to describe the vowels that are lengthened compensatorily and determine the morphological processes that trigger compensatory lengthening in Ekegusii. Guided by native speaker intuition and triangulation by other native speakers, data in the form of nominals and verbals were elicited from four Ekegusii texts and qualitatively analysed for emerging patterns. Findings revealed that all the seven basic Ekegusii vowels undergo compensatory lengthening when their phonetic environments are altered. Vowel compensatory lengthening is brought out as a surface realisation of the interaction of morphemes through the morphological process of prefixation. The lengthening is further seen as a conspiracy to eliminate ill-formed sequences created by prefixation. The height of the first vowel and whether it is followed by another vowel or a consonant determines how the hiatus situation is eliminated. It is expected that the analyses done in this study will have practical pedagogical implications in the teaching of segmental and suprasegmental aspects of Ekegusii.
Full text available online at http://ir-library.ku.ac.ke/bitstream/handle/123456789/8825/The%20Morphophonemics%20of%20Vowel%20Compensatory....pdf?sequence=4&isAllowed=y
Keywords: Compensatory lengthening; Hiatus; Autosegmental phonology; Tier; Morphophonemic processes